2008
DOI: 10.1375/twin.11.2.219
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Outcome and Change in Body Mass Index in Mothers of Dichorionic Twins: A Longitudinal Cohort Study

Abstract: We used a prospective cohort to analyze the effect of change in BMI rather than change in weight, in mothers carrying dichorionic twins from a population that did not receive any dietary intervention. A total of 269 mothers (150 nulliparas and 119 multiparas) were evaluated. The average change (%) from the pre-gravid BMI was 7.2 ± 6.1, 17.4 ± 8.2, and 28.7 ± 10.8, at 12–14, 22–25, and 30–34 weeks, respectively, without difference between nulliparas and multiparas. The comparison between maternities below or ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
1
11
1
Order By: Relevance
“…Preterm birth is the most important obstetric outcome. Many previous studies have investigated this subject and have found an association between GWG and preterm birth [15,[19][20][21][22]. However, the results are conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…Preterm birth is the most important obstetric outcome. Many previous studies have investigated this subject and have found an association between GWG and preterm birth [15,[19][20][21][22]. However, the results are conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…14 In contrast to our study findings, a prospective cohort of twin gestations found no association with weight gain and neonatal outcomes. 15 …”
Section: Commentmentioning
confidence: 99%
“…Furthermore, some studies (Luke, 1998;Luke et al, 2003) used extrapolations of maternal weight gains rather than actual measurements. Others failed to take account of confounders such as maternal pre-pregnancy weights and unrecognised dietary interventions (Simões et al, 2008), as well clinical conditions such as gestational diabetes and preeclampsia.…”
Section: Maternal Weight Gain For Twin Pregnanciesmentioning
confidence: 99%
“…In contrast, Simões et al (2008) examined a prospective cohort of women expecting twins and measured BMI instead of monitoring weight gain. They conducted actual weight measurements and ensured there were no dietary interventions.…”
Section: Maternal Weight Gain For Twin Pregnanciesmentioning
confidence: 99%